Influence of Inlet Groove on Flow Characteristics in Stall Condition of Full-Tubular Pump - Shi, Lijian; Jiang, Yuhang; Cai, Yiping; Chen, Beishuai; Tang, Fangping; Xu, Tian; Zhu, Jun; Chai, Yao (Frontiers in Energy Research, 2022)
The full-tubular pump is a new type of pump with a narrow range of stable operation. In order to improve the internal flow characteristics of the full-tubular pump under small flow conditions and improve the safe and stable operating range of the pump, this paper conducts numerical simulation of the full-tubular pump model based on the Reynolds time-averaged N-S equation and the SST k-ω turbulence model. The improvement mechanism of the parameters of the inlet grooves on the stall area of the full-tubular pump is studied, and the reliability of the numerical simulation of the full-tubular pump is verified by model tests. The research results show that the inlet groove can improve the head and efficiency of the full-tubular pump in the small flow area, and the head at the deep stall condition is increased by nearly 1.61 m. The inlet groove increases the pressure difference of the impeller, which increases the head and improves the hump. At the same time, the increase in the pressure difference of the impeller increases the backflow flow in the gap between the stator and the rotor. The groove can reduce the vortex strength and backflow range at the inlet pipe wall near the stall operating, and also improve the flow field at the impeller inlet. In terms of pressure pulsation, the groove can effectively suppress the low-frequency pressure pulsation at the inlet of the impeller of the full-tubular pump under stall conditions, and effectively reduce the amplitude of the main frequency pressure pulsation and improve the internal flow. The research in this paper can provide a reference for improving the flow characteristics in the stall condition of the full-tubular pump.